Peningkatan Produksi Bioetanol Nira Aren (Arenga pinnata Merr.) Menggunakan Ragi Tempe Selama Proses Fermentasi - Zulkahfi; Niger, Vanto; Azizah, Nur; Sari Parenden, Novita; Thumena, Yeyen; Arfiani Rahim Sila, Sri (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
Ethanol is one of the chemical liquids that is often used in the world of health as a material for making medicines and sterilization materials, in addition this material has also been used as an alternative energy in all fields. Ethanol production so far comes from petroleum which is decreasing and non-renewable. Ethanol development can come from other materials such as abundant and renewable palm sap and can produce a bioethanol product that can replace commercial ethanol. The aim of this study was to detect the quality of palm sap bioethanol obtained from Mombi village using tempe yeast fermentation. The study used an experimental method with a Complete Random Design pattern with yeast/palm sap concentration variables, namely 2 g/200 mL, 6 g/200 mL, 10 g/200 mL, 14 g/200 mL, and control (without yeast mixture). The parameters observed included pH levels, the amount of bioethanol and the alcohol content of bioethanol. The results showed that there was a decrease in the pH value of the palm sap solution after distillation, where there was an increase in acid in the resulting bioethanol product. The average amount of bioethanol produced reaches 48.86% but the alcohol content in the bioethanol is very low, only reaching 15.46%